2016
DOI: 10.1097/sle.0000000000000268
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Liver Resection can be an Effective Way in Obese Patients: A Single Center of 2-Year Experience

Abstract: Obesity should not be seen as a contraindication for laparoscopic liver resection, which is a safe and feasible procedure for obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…This result clearly contrasts that for open resection, suggesting that this surgical approach has distinct advantages in this patient population. Similar observations have been reported in numerous smaller cohort studies of hepatic resection in obese patients 24–27. The laparoscopic approach to hepatic resection dramatically decreases surgical wall trauma, as only five or six port incisions are made, and the resected specimen is extracted without a muscle incision 28.…”
Section: Discussionsupporting
confidence: 78%
“…This result clearly contrasts that for open resection, suggesting that this surgical approach has distinct advantages in this patient population. Similar observations have been reported in numerous smaller cohort studies of hepatic resection in obese patients 24–27. The laparoscopic approach to hepatic resection dramatically decreases surgical wall trauma, as only five or six port incisions are made, and the resected specimen is extracted without a muscle incision 28.…”
Section: Discussionsupporting
confidence: 78%
“…However, LLR in obese patients is considered problematic. Despite this, several reports have stated that obesity should not be a contraindication for LLR [21, 22] and that LLR was less influenced by BMI and was beneficial in obese patients [23, 24]. In our case, despite the patient being severely obese (BMI 40 kg/m 2 ), LLR of the three separate lesions was successfully performed without excessive blood loss.…”
Section: Discussionmentioning
confidence: 62%
“…Normal weight and overweight were considered BMI of <25 and 25–30, respectively 15,16 . The three studies from Japan 17,18,20 and one from China 21 defined obesity as a BMI of ≥25 kg/m 2 . One such study categorized patients with a BMI ≥30 kg/m 2 as highly obese 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Rates of conversion to open laparotomy were examined in four studies (Table 3), ranging from 0% to 31% 16,19–21 . Only one study found rates of conversion were higher in obese patients (31%) compared to normal (11.5%) and overweight (13%) patients ( P = 0.03).…”
Section: Resultsmentioning
confidence: 99%